Linseed oil microencapsulation for advanced corrosion protection coatings: A review - Farasuraya, Che Zakaria; Siti Maznah, Kabeb; Nurul Huda, Abu Bakar; Rahman, Atif Ur (John Wiley & Sons, Inc., 2025)
Corrosion poses a persistent challenge in various industries, necessitating effective protective measures for metal structures. This review not only delves into the overall realm of microencapsulation in corrosion protection but also contributes a unique perspective by extensively examining recent advancements in the microencapsulation of linseed oil. Emphasizing a novel approach, the review introduces advancements in self-healing features, diverse microencapsulation techniques, environmentally friendly shell materials, and the critical role of capsule size and distribution. The study addresses a noticeable gap in the existing literature, aiming to contribute unique insights and solutions to the challenges faced in the field of corrosion protection.